2015
DOI: 10.1111/jicd.12148
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation in oral medicine: a review

Abstract: Photobiomodulation (PBM) or low-level laser therapy (LLLT) in dentistry is an evolving science, with an increasing number of controlled clinical studies exploring its potential as a treatment modality. The present study provides an outline of the biologic mechanism of PBM and summarizes the findings of clinical studies of PBM for specific applications in oral medicine. Controversies and drawbacks associated with PBM, which require further research, are also identified. Current literature reports the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 76 publications
(110 reference statements)
1
41
0
10
Order By: Relevance
“…Currently, many studies show that phototherapy with low power lasers can promote analgesia, cell biomodulation, fibroblast proliferation, collagen synthesis and regeneration of bone and nerve tissues, with significant clinical and histological changes on irradiated biological tissues during the inflammatory and healing processes . With the use of laser phototherapy on the treatment of BMS, symptoms of burning are reported to decrease, providing pain relief and control of the inflammatory process . Recent studies have shown that the therapeutic effects can be reported by the patient immediately after the irradiation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many studies show that phototherapy with low power lasers can promote analgesia, cell biomodulation, fibroblast proliferation, collagen synthesis and regeneration of bone and nerve tissues, with significant clinical and histological changes on irradiated biological tissues during the inflammatory and healing processes . With the use of laser phototherapy on the treatment of BMS, symptoms of burning are reported to decrease, providing pain relief and control of the inflammatory process . Recent studies have shown that the therapeutic effects can be reported by the patient immediately after the irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…With the use of laser phototherapy on the treatment of BMS, symptoms of burning are reported to decrease, providing pain relief and control of the inflammatory process . Recent studies have shown that the therapeutic effects can be reported by the patient immediately after the irradiation . Also, laser acupuncture (660 nm) has also been reported showing that the technique might be useful in patients with BMS .…”
Section: Introductionmentioning
confidence: 99%
“…Elle reste à ce jour une complication fréquente et invalidante chez les enfants de la chimioradiothéra-pie des cancers de la tête et du cou et de la transplantation de cellules souches hématopoïétiques [1,3]. Sa prise en charge reste une préoccupation majeure en cas de survenue aussi bien pour le médecin que le patient.…”
Section: Introductionunclassified
“…Les enfants sont les plus touchés car leur épithélium a un taux mitotique plus élevé. Plusieurs approches thérapeutiques pour la traiter ont été utilisées, mais, aucune intervention n'a été en mesure de prévenir et de traiter elle-même les mucites orales [1][2][3][4][5][6]. Ceci risque d'engager le pronostic vital des enfants cancé-reux nécessitant un traitement leur maladie.…”
Section: Introductionunclassified
“…Low-level laser therapy (LLLT), also known as photobiomodulation is a non-drug, non-invasive clinical application that has been used for treatment of inflammatory disorders (10). It has potential analgesics, anti-inflammatory, immunomodulating and biostimulating effects (12). It has demonstrated several therapeutic effects that can be used for treatment of burning sensation induced by BMS.…”
Section: Management Of Bmsmentioning
confidence: 99%